Archives and citzenship: the access to public information - Ancona Lopez, André Porto (Revista General de Información y Documentación, 2012)
The essay intends to discuss the active role played by archives in order to provide access to public information, considering them as natural custodians of administrative acts evidences, therefore, with a central position on the agenda of transparency and citizenship. The text aims to deal with key concepts of archives and of archival documents in order to discuss some of the relationships among these institutions and society. The right of information access surpasses a broader understanding of the active role of the archives, which cannot be restricted to the administrative state archives but has also to consider private archives with public and social interests, as exemplified by some Brazilians cases. Active and proof dimensions of archival documents are directly related to the four essential characteristics (cohesiveness, naturalness, impartiality and authenticity), as is demonstrated with other examples.